Plasmonic nanostructures fabricated using nanosphere-lithography, soft-lithography and plasma etching - Gonçalves, Manuel R.; Makaryan, Taron; Enderle, Fabian; Wiedemann, Stefan; Plettl, Alfred; Marti, Othmar; Ziemann, Paul (Beilstein Journal of Nanotechnology, 2011)
We present two routes for the fabrication of plasmonic structures based on nanosphere lithography templates. One route makes use of soft-lithography to obtain arrays of epoxy resin hemispheres, which, in a second step, can be coated by metal films. The second uses the hexagonal array of triangular structures, obtained by evaporation of a metal film on top of colloidal crystals, as a mask for reactive ion etching (RIE) of the substrate. In this way, the triangular patterns of the mask are transferred to the substrate through etched triangular pillars. Making an epoxy resin cast of the pillars, coated with metal films, allows us to invert the structure and obtain arrays of triangular holes within the metal. Both fabrication methods illustrate the preparation of large arrays of nanocavities within metal films at low cost.Gold films of different thicknesses were evaporated on top of hemispherical structures of epoxy resin with different radii, and the reflectance and transmittance were measured for optical wavelengths. Experimental results show that the reflectivity of coated hemispheres is lower than that of coated polystyrene spheres of the same size, for certain wavelength bands. The spectral position of these bands correlates with the size of the hemispheres. In contrast, etched structures on quartz coated with gold films exhibit low reflectance and transmittance values for all wavelengths measured. Low transmittance and reflectance indicate high absorbance, which can be utilized in experiments requiring light confinement.
Keywords: nanosphere-lithography; near-field enhancement; plasma etching; soft-lithography; surface plasmons